2018
DOI: 10.18355/xl.2018.11.02.11
|View full text |Cite
|
Sign up to set email alerts
|

Language acquisition through massive open online courses (MOOCs): opportunities and restrictions in educational university environment

Abstract: The article addresses the issue of the use of massive open online courses (MOOCs) in modern universities, their effectiveness in general as well as the restrictions MOOCs have in terms of allowing students to form the same level or a comparable level of competence in studying of various disciplines as the full-time study provides. The author focuses on the implementation of MOOCs in language acquisition and provides empirical study data on the phenomena linked to language acquisition in terms of both didactic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Numerous studies show that openness to experience and especially conscientiousness are significant predictors of academic achievements for most studied subjects, including FL/SL [15][16][17]. Recent Russian research based on the FFM has shown that conscientiousness impacts the academic achievements of Russian university and grade-school students [18][19][20][21]. However, a study of Russian linguistics students' academic achievements in different subjects showed that none of the FFM traits are associated with a student's final grades in English (as the "first" and mandatory FL), while conscientiousness, extraversion, and neuroticism are correlated with the final grades for their "second" elective FL [18].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Numerous studies show that openness to experience and especially conscientiousness are significant predictors of academic achievements for most studied subjects, including FL/SL [15][16][17]. Recent Russian research based on the FFM has shown that conscientiousness impacts the academic achievements of Russian university and grade-school students [18][19][20][21]. However, a study of Russian linguistics students' academic achievements in different subjects showed that none of the FFM traits are associated with a student's final grades in English (as the "first" and mandatory FL), while conscientiousness, extraversion, and neuroticism are correlated with the final grades for their "second" elective FL [18].…”
Section: Introductionmentioning
confidence: 99%
“…In Russian psychology, a large number of FLA studies have been carried out using the System-Functional Model of personality traits developed by Krupnov [22]. Researchers consider sociability, curiosity, persistence, responsibility, and initiative as the FLA factors for different university students [19][20][21][23][24][25]. In particular, it was revealed that persistence is more closely related to success in FLA than curiosity [19,20], and initiative has a contradictory correlation with FLA assessments in linguistics and non-linguistics university students [21,23].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations